Integrating the tumor-suppressive activity of Maspin with p53 in retuning the epithelial homeostasis: A working hypothesis and applicable prospects - Tang, Sijie; Ling, Zhongli; Jiang, Jiajia; Gu, Xiang; Leng, Yuzhong; Wei, Chaohui; Cheng, Huiying; Li, Xiaohua (Frontiers in Oncology, 2022)
Epithelial malignant transformation and tumorous development were believed to be closely associated with the loss of its microenvironment integrity and homeostasis. The tumor-suppressive molecules Maspin and p53 were demonstrated to play a crucial role in body epithelial and immune homeostasis. Downregulation of Maspin and mutation of p53 were frequently associated with malignant transformation and poor prognosis in various human cancers. In this review, we focused on summarizing the progress of the molecular network of Maspin in studying epithelial tumorous development and its response to clinic treatment and try to clarify the underlying antitumor mechanism. Notably, Maspin expression was reported to be transcriptionally activated by p53, and the transcriptional activity of p53 was demonstrated to be enhanced by its acetylation through inhibition of HDAC1. As an endogenous inhibitor of HDAC1, Maspin possibly potentiates the transcriptional activity of p53 by acetylating the p53 protein. Hereby, it could form a “self-propelling” antitumor mechanism. Thus, we summarized that, upon stimulation of cellular stress and by integrating with p53, the aroused Maspin played the epigenetic surveillant role to prevent the epithelial digressional process and retune the epithelial homeostasis, which is involved in activating host immune surveillance, regulating the inflammatory factors, and fine-tuning its associated cell signaling pathways. Consequentially, in a normal physiological condition, activation of the above “self-propelling” antitumor mechanism of Maspin and p53 could reduce cellular stress (e.g., chronic infection/inflammation, oxidative stress, transformation) effectively and achieve cancer prevention. Meanwhile, designing a strategy of mimicking Maspin’s epigenetic regulation activity with integrating p53 tumor-suppressive activity could enhance the chemotherapy efficacy theoretically in a pathological condition of cancer.